Synthesis of silicon dioxide hollow spheres - Gorbik, P.P.; Demchenko, Yu.O.; Dubrovin, I.V.; Kashin, G.N. (Functional Materials, 2009)
The hollow spherical particles of silicon dioxide have been synthesized by hydrolysis of dimethyl dichlorosilane (DMDCS) on the surface of spherical aerosol particles of DMDCS solution in nonpolar solvents. The formation conditions for spherical particles with prespecified structure and morphology have been determined. The phase and chemical composition as well as the morphology of the particles have been examined by X-ray diffraction, Auger electron spectroscopy, scanning electron microscopy, and atomic force microscopy. Порожнисті сферичні частинки діоксиду кремнію синтезовано шляхом гідролізу диметилдихлорсилану (ДМДХС) на поверхні сферичних частинок аерозолю розчину ДМДХС у неполярних розчинниках. Визначено умови формування частинок із заданою структурою та морфологією. Фазовий та хімічний склад та морфологію одержаних частинок досліджено методами рентгенівського фазового аналізу, оже-спектроскопії, растровоі електронноі та атомної силової мікроскопії. Полые сферические частицы диоксида кремния синтезированы путем гидролиза диметилдихлорсилана (ДМДХС) на поверхности сферических частиц аэрозоля раствора ДМДХС в неполярных растворителях. Определены условия формирования частиц с заданной структурой и морфологией. Фазовый и химический состав и морфология полученных частиц исследованы методами рентгеновского фазового анализа, ожеспектроскопии, растровой электронной и атомной силовой микроскопии.